ENHANCING THE SAFETY OF FOREIGN WORKERS THROUGH LANGUAGE DEVELOPMENT AND THE COMPETENT USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES (ICTS) - Iis Kurnia Nurhayati; Alila Pramiyanti; Yuliani Rachma Putri (Fakultas Seni Rupa dan Desain ITB, 2017)
The focus for this research was how the knowledge of a foreign language and the competence in the use of information and communication technologies (ICTs) contributed to the safety of Indonesians working abroad. The study was questionnaire-based research and semi-structured interviews with Indonesian workers working in the informal sectors, particularly as domestic workers in Singapore, Taiwan, Malaysia and Hongkong. The method led to rich correlational and qualitative data providing an in